THE VALORIZATION OF RACIAL INDENTITY IN EARLY CHILDHOODEDUCATION:AN ANALYSIS OF THE BOOK ‘‘THE BEAUTIFUL GILDBOND DEFIT’’ (REMUNOM, 2025)
AbstractValuing racial identity in early childhood education is fundamental to combating prejudice andpromoting respect for diversity. This article analyzes how children's literature can be used as apedagogical tool to strengthen the racial identity of Black children, based on Ana Maria Machado's book"Menina Bonita do Laço de Fita." The research adopts a qualitative approach, with an interpretiveanalysis of the work and is supported by theoretical frameworks on anti-racist education, racial identity,and children's literature, as well as Law No. 10.639/03. The book's narrative presents a Black charactervalued for her beauty, promoting self-esteem, representation, and the breaking of stereotypes. The articlealso shares a personal experience of racism in childhood, highlighting the emotional impact of theseexperiences and the importance of addressing them early. In addition to the main work, books such as"Sulwe" and "The Little Black Prince" are mentioned, which also contribute to the construction ofidentity and self-esteem in Black children. The work highlights the importance of educators' role inmediating these issues and building an anti-racist pedagogy. A project carried out at CEIM Aurora Nunesis also cited as a practical example of promoting ethnic-racial diversity. The conclusion is that children'sliterature, combined with pedagogical projects and initiatives, is essential for Black children topositively recognize themselves and for white children to learn to respect differences, contributing to amore inclusive and respectful school environment.